3D QSAR Studies of DAMNI Analogs as Possible Non-nucleoside Reverse Transcriptase Inhibitors. Issue Volume 5:Issue S2(2008) (2008) - Ganguly, S.; Gopalakrishnan, V.
Abstract : The non-nucleoside inhibitors of HIV -1-reverse transcriptase (NNRTI s) are an important class of drugs employed in antiviral therapy. Recently, a novel family of NNRTI s commonly referred to as 1-[2-diarylmethoxy] ethyl) 2-methyl-5-nitroimidazoles (DAMNI ) derivatives have been discovered. The 3D -QSAR studies on DAMNI derivatives as NNRTI s was performed by comparative molecular field analysis (CoMFA ) and comparative molecular similarity indices analysis (CoMSIA ) methods to determine the factors required for the activity of these compounds. The global minimum energy conformer of the template molecule 15, the most active molecule of the series, was obtained by simulated annealing method and used to build the structures of the molecules in the dataset. The combination of steric and electrostatic fields in CoMSIA gave the best results with cross-validated and conventional correlation coefficients of 0.654 and 0.928 respectively. The predictive ability of CoMFA and CoMSIA were determined using a test set of ten DAMNI derivatives giving predictive correlation coefficients of 0.92 and 0.98 respectively indicating good predictive power. Further, the robustness of the models was verified by bootstrapping analysis. The information obtained from CoMFA and CoMSIA 3D contour maps may be of utility in the design of more potent DAMNI analogs as NNRTI s in future.